Do knowledge management and innovative work behavior enhance organizational performance? The role of employee competence - Yuddy Giovanna Priscilla; Fellia Rivanti (Universitas Ahmad Dahlan, 2026)
This study examines the impact of knowledge management and innovative work behavior on employees' competencies and organizational performance in Indonesia's electronic manufacturing sector. This research is driven by the ongoing disparity between labor market requirements and the qualifications of the available workforce, especially in Batam City, Indonesia, where inadequate competency levels hinder the workforce's capacity to fulfill industry demands. This research is unusual in its emphasis on electronic manufacturing firms in Batam City, Indonesia, an environment that has received less scholarly scrutiny, particularly regarding human resource practices and their relationship to organizational performance. To ensure representativeness, the study employed a probability sample method, specifically non-probability purposive sampling, to recruit 210 respondents from diverse departments. Data analysis in this study was conducted using SmartPLS, with data collected via a survey. The results show that knowledge management and innovative work behavior significantly improve employee competency, while innovative work behavior also positively affects organizational performance. However, knowledge management and employee competency do not significantly influence organizational performance. Additionally, employee competency does not mediate the relationships between the variables. In conclusion, innovative work behavior plays a key role in enhancing organizational performance, whereas knowledge management mainly contributes to improving employee competency rather than directly impacting performance. The study emphasizes the need to fortify human resource management strategies and advocates establishing a triple helix innovation program that fosters collaboration among government, corporations, and universities to improve employee competencies, attract investment, and bolster Indonesia's economic growth.